Application of a 2D Molybdenum Telluride in SERS Detection of Biorelevant Molecules; ACS Applied Materials and Interfaces; Vol. 12, iss. 42 - Fraser J. P. James; Postnikov P. S. Pavel Sergeevich; Milyutina (Miliutina) E. V. Elena Vadimovna; Kolska Z. Zdenka; Valiev R. R. Rashid Rinatovich; Svorcik V. Vaclav; Lyutakov O. Oleksy; Ganin A. Y. Alexey; Guselnikova O. A. Olga Andreevna (2020, 2020)
Title screen